2014
DOI: 10.1007/s12033-014-9802-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of ISSR Markers to Analyze Molecular Relationships in Iranian Jasmine (Jasminum spp.) Accessions

Abstract: There are many species of jasmines in different regions of Iran in natural or cultivated form, and there is no information about their genetic status. Therefore, inter-simple sequence repeat (ISSR) analysis was used to evaluate genetic variations of the 53 accessions representing eight species of Jasminum collected from different regions of Iran. A total of 21 ISSR primers were used which generated 981 bands of different sizes. Mean percentage of polymorphic bands was 90.64 %. Maximum resolving power, polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
6
13
0
Order By: Relevance
“…This values also agree with AFLP studies done with other forage grass such as Dactylis glomerata [47] and Phalaris aquatica [48]. The Marker index (MI) and resolving power (RP), two importantly alternative parameters in selecting informative markers for diversity studies [49, 50], had also displayed high efficiency of AFLP markers in unveiling polymorphisms in E. tangutorum germplasm. A very strong and positive correlation observed among PIC, RP and MI value in present work indicates the use of any of three parameters to screen the informative primer combinations [38]; although the relationship between the informativeness of molecular markers for identifying germplasms and these marker parameters is not totally clear [46].…”
Section: Discussionsupporting
confidence: 83%
“…This values also agree with AFLP studies done with other forage grass such as Dactylis glomerata [47] and Phalaris aquatica [48]. The Marker index (MI) and resolving power (RP), two importantly alternative parameters in selecting informative markers for diversity studies [49, 50], had also displayed high efficiency of AFLP markers in unveiling polymorphisms in E. tangutorum germplasm. A very strong and positive correlation observed among PIC, RP and MI value in present work indicates the use of any of three parameters to screen the informative primer combinations [38]; although the relationship between the informativeness of molecular markers for identifying germplasms and these marker parameters is not totally clear [46].…”
Section: Discussionsupporting
confidence: 83%
“…However, in the present study, we have obtained highest CCC value of 0.9216 which is associated with acceptable genetic similarity matrix. Similarly, Ghasemi Ghehsareh et al ( 2015 ) also obtained highest CCC value of 0.9968 in 53 genotypes representing eight species collected from Iran using microsatellite markers.…”
Section: Discussionmentioning
confidence: 80%
“…Prevost and Wilkinson (1999) found that Rp can be used to evaluate the ability of each primer for differentiating among several accessions. In general, primers with a higher Rp value can better distinguish among accessions (Ghasemi Ghehsareh et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of each primer to differentiate between accessions was assessed by calculating their resolving power [Rp (Deore and Samantaray, 2015;Gilbert et al, 1999)], marker index [MI (Ghasemi Ghehsareh et al, 2014;Powell et al, 1996)], and polymorphic information content [PIC (Deore and Samantaray, 2015;Ghasemi Ghehsareh et al, 2014;Weising et al, 2005)]. PIC was calculated as PIC = 1 -pi 2 -qi 2 , where p is the band rate and q is no band rate (Chadha and Gopalakaishna, 2007;Deore and Samantaray, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation